2010
DOI: 10.1002/chem.200902986
|View full text |Cite
|
Sign up to set email alerts
|

A HTS Assay for the Detection of Organophosphorus Nerve Agent Scavengers

Abstract: A new pro-fluorescent probe aimed at a HTS assay of scavengers is able to selectively and efficiently cleave the P-S bond of organophosphorus nerve agents and by this provides non-toxic phosphonic acid has been designed and synthesised. The previously described pro-fluorescent probes were based on a conventional activated P-Oaryl bond cleavage, whereas our approach uses a self-immolative linker strategy that allows the detection of phosphonothioase activity with respect to a non-activated P-Salkyl bond. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 131 publications
0
21
0
Order By: Relevance
“…Oximes are well-known antidotes for the treatment of OP poisonings. Their mode of action involves reactivation of the OP-inhibited acetylcholinesterase [29], yet previous work has also indicated that certain oximes are able to cleave OPs directly [30]. We show that some of our cyclodextrin derivatives efficiently reduce GF concentrations in solution under physiological conditions within seconds, thus preventing the OP from inhibiting AChE.…”
Section: Introductionmentioning
confidence: 80%
“…Oximes are well-known antidotes for the treatment of OP poisonings. Their mode of action involves reactivation of the OP-inhibited acetylcholinesterase [29], yet previous work has also indicated that certain oximes are able to cleave OPs directly [30]. We show that some of our cyclodextrin derivatives efficiently reduce GF concentrations in solution under physiological conditions within seconds, thus preventing the OP from inhibiting AChE.…”
Section: Introductionmentioning
confidence: 80%
“…Since their introduction in 1981, [11][12][13][14][15][16][17] self-immolative spacers found applications in prodrugs, [4,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] sensors for chemicals or enzymes, [33][34][35][36][37][38][39][40][41] and for drug delivery. [26-28, 30-32, 42-46] Self-immolative spacers are also increasingly used in materials science, [47][48][49][50][51] where their unique feature of kinetically programmable auto-destruction provides unprecedented opportunities for sustainable matter management( i.e.…”
Section: Introductionmentioning
confidence: 99%
“…73 It is able to cleave the P-S bond of OP thereby yielding to the corresponding isoxazole analogue and non-toxic phosphonic adduct, thus through this preventing recapture phenomena. 74 The two uncharged oximes (35 and 36) as shown in Fig. 16, had a superior or similar in vitro ability to reactivate AChE inhibited by VX and tabun as compared to HI-6, obidoxime, TMB-4 and HLö À7.…”
Section: Development Of Uncharged Oximesmentioning
confidence: 95%
“…45 Salicylaldoximes are known to be able to quickly cleave the P-S bond of organophosphates and avoid the re-inhibition phenomenon in their reactivation process, but salicylaldoximes lack reactivation ability due to their poor affinity for. 74 By using the dual binding site strategy, several PSLs were conjugated with salicylaldoximes as shown in Fig. 26 in order to increase their affinity.…”
Section: Development Of Uncharged Oximesmentioning
confidence: 99%